Labial Adhesions Causing Recurrent Urinary-Tract Infections in an Elderly Woman - Masashi Takemaru; Noriko Aramaki-Hattori; Chisato Tsue; Kazuo Kishi (Case Reports in Medicine)
A 91-year-old postmenopausal woman with a prior history of two labial-adhesion separations suffered from recurrent urinary-tract infections. We were able to successfully treat her labial adhesions using surgery.